The effect of including plantain (Plantago lanceolata L.) in perennial ryegrass and white clover pastures on milk production and nitrogen excretion of dairy cows throughout the grazing season - C.T. Minogue; T.M. Boland; I. Etxeberria; N.A. Walsh; A.G. Fahey; M. Dineen; Z.C. McKay (Journal of Dairy Science)
ABSTRACT: The objective of this study was to investigate the effect of including plantain (Plantago lanceolata L.; PL) in a perennial ryegrass (Lolium perenne L.; PRG) and white clover (Trifolium repens L.; WC) pasture mixture grazed by dairy cows on DMI, milk production and composition, and N excretion throughout the grazing season. Twenty-six (6 primiparous and 20 multiparous) Holstein-Friesian dairy cows were blocked on parity and assigned to 1 of 2 dietary treatments, balanced for economic breeding index, calving date, BW and BCS at calving, and milk production. Treatments were PRG and WC pasture (GrC) and PRG, WC, and PL pasture (GCP), supplemented with concentrate feed at milking (daily at 0730 and 1500 h). Cows grazed their allocated pasture from d 4 postpartum until the end of the grazing season (34-wk study). Nitrogen excretion was quantified during 2 N partitioning studies; conducted when cows were in early lactation (EL; 61 ± 11 DIM; wk 10) and late lactation (LL; 214 ± 11 DIM; wk 32). Cows offered GCP had a 6% lower daily milk solids yield in EL but a 9% greater daily milk yield in LL. Milk fat concentration was significantly lower from cows offered GCP in EL and LL. Treatment did not significantly affect cumulative milk, milk fat, or milk protein yield per cow, however, cows offered GCP had a numerically lower cumulative milk solids yield (451 kg/cow vs. 433 kg/cow for GrC and GCP respectively). For cows grazing GCP, estimated pasture DMI tended to be greater in the EL N partitioning study (+8%) and was significantly greater in the LL N partitioning study (+17%). Dietary PL content was ∼33% and 32% of GCP cows' total DMI in the EL and LL N partitioning studies. For cows offered GCP, N utilization efficiency tended to be 12% lower in the EL N partitioning study, but 13% greater in the LL N partitioning study. Estimated total urine volume was greater in both N partitioning studies for cows grazing GCP, and urinary N excretion (−30%) and concentration (−39%) were only lower in the LL N partitioning study for cows on the GCP treatment.